Jenis-Jenis Burung yang Memanfaatkan Eurya acuminata DC Di Kampus Universitas Andalas Limau Manis, Padang - Dewi Chandrarini Surya; Wilson Novarino; Ardinis Arbain (Universitas Andalas, 2013)
An inventory of birds visiting Jirak (Eurya acuminata) at Limau Manis Padang was done from July to December 2011. The study used point sampling method to collect birds data and determine birds frequency that visited Jirak (Eurya acuminata). This study found 12 birds species, which belong to two orders, seven families and eight genera. Pycnonotus goiavier was the most frequent visitor. Eurya acuminata was more widely visited for foraging (71.47%), followed by perching (17.40%) and singing (11.13%). The birds mainly visited Eurya acuminata more often in the morning (54.16%) rather than afternoon (45.83%). The top of the canopy area was preferred (45.93%) rather than margin canopy (37.19%) and the center of the canopy (16.86%).Keywords : inventory of birds, Eurya acuminata, canopy